DendrochronologicaI Studies of white spruce in the northern Yukon, Canada - Earles, Sean Patrick (Scholarship@Western, 2008)
This thesis investigates the variation of ring widths from 23 white spruce (Picea glauca) treeline chronologies located along the Dempster Highway (61 -68Â°N), bracketing the position of the classical TTHH site (65.33Â°N) in the Yukon. Relationships between the 18 strongest chronologies and mean monthly/seasonal temperatures from Dawson over the 1900-2000 period were examined using correlation analyses. Ring-width chronologies were commonly negatively correlated with prior summer temperatures over the entire 20th century but most strongly in the 1950-2000 period. However, several sites had positive relationships with summer temperatures in the 1900-1950 period and much weaker or negative relationships with summer temperatures over the 1951-2000 period indicating an apparent â€œdivergentâ€ response over the 20th century. â€œResponder analysisâ€ of three highly replicated sites indicated two were dominated by strong negative relationships with summer temperatures in the late 20th century but the northernmost site contained trees that maintained a positive relationship with summer temperatures in the late 20th century.